The association between energy-adjusted dietary inflammatory index (E-DII) and lung cancer in 101,755 participants aged 55 years and above: a large prospective cohort - Yangpiaoyi Shi; Wanhao Tan; Yi Xiao; Linglong Peng; Zhiquan Xu; Hang Liu; Qi Wei; Yaxu Wang; Ling Xiang; Haitao Gu (BMC Public Health)
Abstract Background The association between the Dietary Inflammatory Index (DII) and lung cancer incidence remains unclear. This inconsistency may be attributed to not considering total energy intake and dietary supplement use adequately. To provide reliable evidence, we conducted a secondary analysis of data from the prospective Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial to examine the association between lung cancer incidence and E-DII (Energy-adjusted DII) derived from both food and supplements as well as from food only. Methods The data of participants were retrieved from the PLCO Cancer Screening Trial. Cox regression analysis was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the incidence of lung cancer and its subtypes, including non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). Additionally, Restricted Cubic Spline (RCS) were used to describe the linear dose-response relationship between lung cancer and its subtypes across the entire EDII score range, subgroup analyses were conducted to identify potential modifiers, and sensitivity analyses were performed to strengthen the stability of our results. Results Over a median follow-up duration of 9.40 years, totally 1,706 incident cases of lung cancer were identified. Our analyses demonstrated that both higher E-DII from food and supplements (HR Q4 vs. Q1: 1.31, 95%CI: 1.14, 1.52, Ptrend = 0.002) and E-DII from food only (HR Q4 vs. Q1: 1.39, 95%CI: 1.22, 1.58, Ptrend <0.001) were associated with an elevated lung cancer incidence. RCS revealed a linear dose-response relationship between both overall lung cancer incidence (Pnonlinearity = 0.509) and NSCLC incidence (Pnonlinearity = 0.489) and E-DII from food and supplements. However, a significant inverse U-shaped association between E-DII from food and supplements SCLC was exhibited (Pnonlinearity = 0.016). The results of the subgroup analyses showed that smoking quantity reveals significant interactions between lung cancer and E-DII from food only (Pinteraction = 0.039). Finally, sensitivity analyses reinforced the robustness of our findings. Conclusion Our findings revealed a positive association between E-DII and lung cancer incidence among U.S. adults aged 55 years and older, particular in populations with higher smoking exposure, which suggesting dietary inflammatory potential may represent an important modifiable risk factor for lung cancer prevention. Furthermore, our analyses demonstrated that SCLC and NSCLC exhibit distinct inflammatory response patterns, indicating potential differences in their biological mechanisms.